Application of intermediate frequency pulse electrical stimulation combined with ultrasound drug delivery in blind insertion of spiral naso-intestinal tube in critically ill neurological patients (中频脉冲电刺激联合超声药物导入在神经重症患者盲插螺旋型鼻肠管中的应用) - LU Yanhua (鲁艳华); SHI Tian (史甜) (中西医结合护理)
Objective To investigate the application effect of intermediate frequency pulse electrical stimulation combined with ultrasound drug delivery in blind insertion of spiral naso-intestinal tube among critically ill neurological patients. Methods From March 2020 to February 2021, 95 patients underwent enteral nutrition in the Neurological Intensive Care Unit were selected as the research objects, and they were divided into observation group (n=48) and control group (n=47) by digital randomization method. The control group was given an intravenous bolus of gastric motility drugs (metoclopramide hydrochloride injection 10 mg), and the observation group was given intermediate frequency pulse electrical stimulation combined with ultrasound drug delivery. The success rate of the first and second catheterization and the curative effect of constipation were compared between the two groups. Results The observation group had a higher success rate for the first placement of the blind-inserted spiral naso-intestinal tube than the control group (79. 17 vs. %46. 81%, P＜0. 01). Among the failed cases of placement in the control group, the success rate of placement by intermediate frequency pulse electrical stimulation combined with ultrasound drug delivery was 76. 00%(19/25). The effective rate of treating constipation in the observation group was higher than that of the control group(P＜0. 05). Conclusion The use of intermediate frequency pulse electrical stimulation combined with ultrasound drug delivery has a significant effect on increasing the success rate of blind insertion of spiral naso-intestinal tubes in critically ill neurological patients, and the success rate in the second catheterization is also high. It can promote gastrointestinal peristalsis and relieve the patients' constipation symptoms. (目的 探讨中频脉冲电刺激联合超声药物导入在神经重症患者盲插螺旋型鼻肠管中的应用效果。方法 选取2020年3月-2021年2月医院神经重症监护室行肠内营养治疗95例患者为研究对象, 采用数字随机法将其分为观察组(n=48)和对照组(n=47)。对照组给予静脉推注促胃动力药物(盐酸甲氧氯普胺注射液10 mg), 观察组给予中频脉冲电刺激联合超声药物导入。比较两组患者首次、二次置管成功率, 评价干预便秘的效果。结果 观察组72 h首次置管成功率79. 17%(38/48), 对照组为46. 81%(22/47), 差异有统计学意义(P＜0. 01)。对照组首次置管失败后, 采用观察组方法进行二次置管, 累计置管成功率为76. 00%(19/25)。评价干预便秘的效果, 观察组总有效率高于对照组(P＜0. 05)。结论 采用中频脉冲电刺激联合超声药物导入提高神经重症患者首次盲插螺旋型鼻肠管置管成功率效果明显, 在二次置管中成功率也较高, 能够促进胃肠蠕动, 改善患者便秘症状。)